PENGARUH PEMBELAJARAN AKIDAH AKHLAK TERHADAP KARAKTER TANGGUNG JAWAB PESERTA DIDIK KELAS VII DI MTS AL-I’ANAH KOSAMBI - Putri, Rahmawati; Karyawati, Lilis; Karnia, Nia (Universitas Islam Negeri Sumatera Utara Medan, 2023)
There are still students who lack self-discipline to become the driving force behind this research. While learning is a process designed by the teacher to help students think creatively and obtain new information in order to improve mastery of subject matter. Students who model reliable behavior should acquire and expand their self-confidence as they learn moral convictions. By examining these issues, the title of this research is